Assessment of Speed Limit Locations Using Crowdsourced Probe Vehicle Data. Issue 1 (January 2015) - Remias, Stephen M.; Mekker, Michelle; McNamara, Margaret; Sturdevant, James R.; Cox, Edward D.; Bullock, Darcy M.
Recently there has been an increased interest in using technology to apply variable speed limit techniques to Interstate roadways. An important component of changing speed limit signs (or variable speed limit signs) is an outcome assessment that collects measured data for understanding the effect on the network. For 265 mi of I-65 in Indiana, the speed limit locations were geolocated and paired with crowdsourced probe vehicle data to develop metrics that engineers and decision makers could use to optimize speed limit placement. Four case studies show the effect of different types of speed reduction and opportunities to improve the current placement. The visual performance measures described in this paper are readily deployable and scalable to any freeway in the country for assessing variable speed limits, work zone speed limits, and static speed limits.